89 Upper extremity musculoskeletal pain in Lebanese bakery workers. (11th October 2013) - Habib, R
Abstract : Background: Musculoskeletal (MS) pain in the upper extremities is a major cause of morbidity among workers in many occupations. Research links upper extremity pain of the shoulder, neck, wrists, and elbow with physical exertion in the workplace and psychosocial influences like workplace organisation. Lebanon's bakery industry is an important occupational environment to explore MS pain as it features cramped spaces, highly pressured work tasks, and frequent engagement of the upper extremities. Studies assessing musculoskeletal pain among workers are rare in Lebanon, as are studies of bakery workers from developing countries. This study assesses the magnitude of upper extremity musculoskeletal pain among Lebanese bakery workers and determines associations with physical and psychosocial variables. Methods: Surveys were conducted among 504 randomly selected bakeries across Lebanon between April and November of 2010. Samples were proportionate to the number of bakeries in each district of the country. Surveys were administered through face-to-face interviews at the workplace with the consent of employers and workers. The survey included items on musculoskeletal pain, general health, workplace activities and organisation, and socio-demographics. Descriptive and logistic regression analyses were completed using SPSS 20.0. Results: Almost 23% of workers reported upper extremity pain. Workers reporting poor self-rated health or chronic illness were twice as likely to report painful symptoms, while workers holding a second job were also twice as likely to have MS pain. Workers engaging in tasks with their hands above their shoulders (OR: 2.58; CI: 1.45–4.58) or repeated wrist movements (OR: 2.68; CI: 1.07–6.70) were more likely to report MS pain. Conclusions: Physical exertions were correlated with upper extremity MS pain. These results indicate a need to focus future interventions on improving workplace ergonomic conditions and implement workplace safety training in Lebanese bakeries.